Identification of novel candidate loci and genes for seed vigor-related traits in upland cotton (Gossypium hirsutum L.) via GWAS - Li, Libei; Hu, Yu; Wang, Yongbo; Zhao, Shuqi; You, Yijin; Liu, Ruijie; Wang, Jiayi; Yan, Mengyuan; Zhao, Fengli; Huang, Juan; Yu, Shuxun; Feng, Zhen (Frontiers in Plant Science, 2023)
Seed vigor (SV) is a crucial trait determining the quality of crop seeds. Currently, over 80% of China's cotton planting area is in Xinjiang Province, where a fully mechanized planting model is adopted, accounting for more than 90% of the total fiber production. Therefore, identifying SV related loci and genes is crucial for improving cotton yield in Xinjiang. In this study, three seed vigor-related traits, including germination potential (GP), germination rate (GR), and the germination index (GI), were investigated across three environments in a panel of 355 diverse accessions based on 2,261,854 high-quality single-nucleotide polymorphisms (SNPs). A total of 26 significant SNPs were detected and divided into six quantitative trait locus (QTL) regions, including 121 predicted candidate genes. By combining gene expression, gene annotation and haplotype analysis, 2 novel candidate genes (Ghir_A09G002730 and Ghir_D03G009280) within qGR-A09-1 and qGI/GP/GR-D03-3 were associated with vigor-related traits, and Ghir_A09G002730 was found to be involved in artificial selection during cotton breeding by population genetic analysis. Thus, understanding the genetic mechanisms underlying seed vigor-related traits in cotton could help increase the efficiency of direct seeding (DS) by molecular marker-assisted selection (MAS) breeding.